Simulation Experiment of High-Temperature and High-pressure Supercritical CO2-Saline Water-Rock Reaction in Deep Volcanic Rocks in the Southern Part of Songliao Basin - Shou, Qianru; Zheng, Sen; Wang, Mengqi (International Journal of Natural Resources and Environmental Studies, 2025)
In order to study the effect of high-temperature and high-pressure CO2 on the physical properties of deep volcanic rock reservoirs in the southern Songliao Basin, a closed-system temperature and pressure co-controlled water-rock reaction simulation method was used to simulate formation temperatures (120°C, 130°C, 140°C) and formation pressures (20MPa, 60MPa) conditions, 6 groups of supercritical CO2-water-rock reaction experiments were carried out. The pore characteristics of the reservoir rock samples before and after the reaction were analyzed using QEMSCAN and scanning electron microscopy to determine the modi-fication of reservoir properties due to the water-rock reaction after CO2 injection into deep volcanic reser-voirs. The experimental results show that the water-rock reaction reaches equilibrium after 96 hours. Super-critical CO2 has different dissolution effects on rock samples at different temperatures and pressures, with a maximum dissolution rate of 0.2803 and a maximum increase in porosity of 5.18%. Supercritical CO2 dis-solved in water forms an acidic environment that has a strong acid etching and remolding effect on rock samples, indicating that the high-temperature, high-pressure supercritical CO2-water-rock reaction is initially dominated by calcite dissolution, followed by dolomite and feldspar minerals dissolve slowly, and quartz minerals are not significantly altered. This experiment shows that selecting representative samples to carry out simulated water-rock reaction experiments under deep formation conditions is an effective and scientific reservoir modification method. In the current context of high cost, high risk, and high investment in deep oil and gas exploration, the results of the high temperature and high-pressure supercritical CO2-water-rock reac-tion experiment have essential reference value for the next step of deep reservoir exploration and develop-ment.